Calcium signalling : a practical approach - Tepikin, Alexei (Oxford University Press, 2001)
Univ. of Liverpool, UK. Revised edition of Cellular Calcium, by James G. McCormack, c1991. Presents the applications of fluorescent and bioluminescent techniques for studies of calcium signalling and calcium-dependent processes. Also discusses problems of fluorescent calcium measurements. Softcover, hardcover available. DNLM: Calcium.
Practical approach series ; 246
Keywords: Fluorescence; Calcium Channels; biomedicínské inženýrství; biologie; fluorescence; vápníkové kanály